Methods of using activin receptor type II signaling inhibitors - ROVALDI CHARLES R; RUDGE JOHN; FURUTANI EDOARDO; SEEHRA JASBIR SINGH (2024)
The present invention provides a method of treating a subject having a hemopenia associated with myelodysplastic syndrome, a hemopenia associated with chronic myelomonocytic leukemia, or a hemopenia associated with myelofibrosis, such as anemia, thrombocytopenia, or neutropenia, the methods are carried out by administering to the subject an ActRII signaling inhibitor, such as an ActRIIA ligand trap that includes an extracellular ActRIIA variant. The extracellular ActRIIA variant may be fused to an Fc domain or portion. 本发明提供了治疗患有与骨髓发育异常综合征相关的血细胞减少症、与慢性骨髓单核细胞性白血病相关的血细胞减少症或与骨髓纤维化相关的血细胞减少症，诸如贫血、血小板减少症或嗜中性粒细胞减少症的受试者的方法，所述方法通过向所述受试者施用ActRII信号传导抑制剂，诸如包括细胞外ActRIIA变体的ActRIIA配体阱来进行。所述细胞外ActRIIA变体可融合至Fc结构域或部分。